Pertumbuhan Cabai Merah (Capsicum annuum L.) pada Tanah Masam yang Diinokulasi Mikoriza Vesikula Arbuskula (MVA) Campuran dan Pupuk Fosfat - Maryam Jamilah; Purnomowati Purnomowati; Uki Dwiputranto (Fakultas Biologi | Universitas Jenderal Soedirman, 2016)
This research aimed to find out the interaction effect between mixed Vesicular Arbuscular Mycorrhiza (VAM) and phosphate fertilizer to the growth of red chili (C. annuum) in acid soil, and to fnd out the best combination of mixed VAM and phosphate fertilizer to the growth of red chili (C. annuum) in acid soil. This research used an experimental method with Completely Randomized Design (CRD) in a factorial pattern with two factors. The first factor was mixed VAM dosages consisted of four levels: 0; 10; 15; 20 g/plant. The second factor was phosphate fertilizer dosages consisted of four levels: 0; 0,2; 0,4; 0,6 g/plant. Each combination treatment had three replication. The parameters were observed in the form of plant height, stem diameter, plant top dry weight, degree of VAM infection, and P content of plant tissue. Data obtained from the observation was analyzed with Analysis of Variance (ANOVA) at an error rate of 5% and 1%, treatment that showed significant or very significant result, then followed with Honestly Significant Difference (HSD) test. The result showed that interaction between mixed Vesicular Arbuscular Mycorrhiza (VAM) and phosphate fertilizer did not increase the plant height, stem diameter, and plant top dry weight, but each factor increased the plant height, stem diameter, and plant top dry weight. VAM dosage inoculation of 20 g/plant without phosphate fertilizer is the most effective combination in increasing the degree of VAM infection.